Business Model Innovation for Non-formal Education Service at High School Level: A Case Study of OPSI Tutoring Center - Saragih, J Erwin (Sekolah Tinggi Manajemen IPMI, 2025)
This study examines business model innovation in the non-formal education sector, focusing on OPSI Tutoring Center. Using a case study approach with mixed methods, data were collected through interviews, observations, and institutional documents, analyzed using the Business Model Canvas (BMC) and SWOT analysis. Findings show that OPSI has a strong value proposition through outcome-based programs, but faces challenges in distribution channels and income stability. The SWOT analysis highlights opportunities for hybrid learning models, digital expansion, and strategic partnerships. Strategic recommendations include improving customer interaction, strengthening internal evaluation, and integrating digital technology in operations and marketing. This research provides practical insights for innovation strategies in Indonesia’s non-formal education sector, supporting institutions in navigating digital transformation and achieving sustainable competitiveness.